Implementation Of Infrastructure Policies to Support Safe and Sanitary Housing in Depok City Area - Dudi Mi’raz Imaduddin; Ismail Nurdin; Muchlis Hamdi; Hadi Prabowo; Kusworo Kusworo; Amelia Shafa Ath Thaariq (Institut Pemerintahan Dalam Negeri, 2023)
Abstract Depok City in an effort to create a clean, comfortable, safe and healthy area, it is necessary to form and organize a Healthy City. Depok City area, especially areas that have slum settlements, are polluted by polluted soil, water and the environment. This condition occurred in 73 areas where soil and water samples were taken for laboratory tests.In order to realize the implementation of Healthy Cities, it is necessary to support physical quality, social environment, changes in people's behavior through the active role of the community and the private sector as well as the Regional Government in a directed, coordinated, integrated and sustainable manner. The goal is to know about the implementation of Settlement Infrastructure Policy in Depok City, what are the inhibiting and supporting factors of the implementation, and what is the suitable implementation Model to achieve Proper and Safe Sanitation in Depok City Area. The method used is qualitative with data triangulation. The data were obtained from interviews conducted with beneficiaries of sanitation development, sub-district officials, sub-district officials, and officials assigned to the Depok City Government. The research findings indicate the implementation of Settlement Infrastructure Policy in Depok City exhibit a commendable level of overall adherence and garners a favorable response from the beneficiary community; sanitation development lacks public interest and funding, resulting in poor community facilities and limited awareness about clean sanitation; and the suitable model draws heavily from Grindle’s model. Keywords: Adequate and Safe Sanitation; Infrastructure; Slum Area.